(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the outcomes of laparoscopic distal gastrectomy with D2 lymphadenectomy and Billroth II reconstruction in the treatment of gastric adenocarcinoma at Nghe An General Friendship Hospital. Methods: A descriptive study was conducted on 90 patients who underwent totally laparoscopic surgery from 2022 to 2024. Parameters analyzed included early postoperative outcomes, histopathological findings, complications, recurrence, survival, and postoperative quality of life. Results: The laparoscopic procedure was completed in 100% of cases with no intraoperative mortality. The early complication rate was low (5.6%). The overall survival rate at 36 months was 78.8%. The recurrence/metastasis rate was 16.7%. Postoperative endoscopic findings and quality of life assessments were generally favorable. Conclusion: Laparoscopic distal gastrectomy with D2 lymphadenectomy and Billroth II reconstruction is a safe, effective, and feasible technique that can be widely applied in the treatment of gastric adenocarcinoma.